ANALISIS KOMPONEN VISUAL PESAN MASKULINITAS PADA SERIES PEAKY BLINDERS SEASON 6 - Reza Gunawan; Anita Pahlevi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The purpose of this study is to identify aspects of the message of masculinity in the series of Peaky Blinders season 6 using the concept 5c’s of cinematography 5c proposed by Joseph V Mascelli. The results of this study, was found out of that the dominant element is the big wheel as this element is present in every episode, while the rarest is be a sturdy oak. Then it was also proven that how the 5C technique in cinematography managed to convey a message. Such as the angle of placement of a high angle camera that describes how a character is being bullied, a low angle that describes the valor of a character; Unsuccessful image continuity without scene by scene so that the image does not feel sloppy; The technique of cutting images or cutting which is also able to give meaning to each transition from the scene and the shot; The distance from the camera that frames the gesture or body language of a character, the audience only sees what the filmmaker wants to show; then the composition technique applied by the filmmaker to add an aesthetic element to each shot image.